PERAN GURU DALAM IMPLEMENTASI SISTEM AMONG DI SD NEGERI 01 MULYOHARJO - Shofa Fuadi; Urip Suwarniti; Soedjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the role of teachers in implementing the among system at SD Negeri 01 Mulyoharjo based on the Ki Hadjar Dewantara Among System. The research method used is qualitative, with data collection techniques through observation, in-depth interviews and documentation. The research results show that the role of teachers is very important in implementing the Ki Hadjar Dewantara Among System which is related to the principles of Ing Ngarso Sung Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handayani. Meanwhile, the role of teachers in this case includes: educator, manager and facilitator. This research concludes that teachers have an important role in implementing the among system at SD Negeri 01 Mulyoharjo which has been implemented in various ways. The role of teachers in implementing the among system in state elementary schools on the principle of Ing Ngarso Sung Tulada is implemented by exemplary discipline, exemplary ethics and exemplary manners. Then the teacher's role in implementing the among system in state elementary schools based on the principle of Ing Madya Mangun Karsa is implemented by building motivation in learning, opening space for discussion in learning, and designing fun learning. Meanwhile, the role of teachers in implementing the among system in state elementary schools based on the Tut Wuri Handayani principle is implemented by creating conducive learning, creating comfortable learning, and developing students' potential.